2015
DOI: 10.1002/pros.23140
|View full text |Cite
|
Sign up to set email alerts
|

NF‐κB and androgen receptor variant expression correlate with human BPH progression

Abstract: Background Benign prostatic hyperplasia (BPH) is a common, chronic progressive disease. Inflammation is associated with prostatic enlargement and resistance to 5α-reductase inhibitor (5ARI) therapy. Activation of the nuclear factor-kappa B (NF-κB) pathway is linked to both inflammation and ligand-independent prostate cancer progression. Methods NF-κB activation and androgen receptor variant (AR-V) expression were quantified in transition zone tissue samples from patients with a wide range of AUASS from incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 68 publications
1
59
1
2
Order By: Relevance
“…In prostate cancer SRD5A1 and SRD5A2 predict biochemical recurrence and reduced efficacy of androgen deprivation therapy . In a previous study , we demonstrated that both activation of NF‐κB and subsequent induction of AR‐V7, contributed to resistance to a 5ARI. Here we examine whether the induction of SRD5A expression could also be a player in this phenomenon.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In prostate cancer SRD5A1 and SRD5A2 predict biochemical recurrence and reduced efficacy of androgen deprivation therapy . In a previous study , we demonstrated that both activation of NF‐κB and subsequent induction of AR‐V7, contributed to resistance to a 5ARI. Here we examine whether the induction of SRD5A expression could also be a player in this phenomenon.…”
Section: Discussionmentioning
confidence: 87%
“…Expression of AR‐V7 is predictive of resistance to Enzalutamide and abiraterone acetate in prostate cancer patients . Gao has reported that AR‐Vs can be produced in response to the non‐canonical NF‐κB pathway, and we have shown that AR‐Vs can be induced by the canonical NF‐κB pathway . Currently, however there is not an established mechanistic link between NF‐κB and resistance to 5ARI therapy in BPH.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…This gains support by the work of Austin et al . , who indicated an upregulation of NF‐κB signaling in prostate tissue specimens from patients with BPH. Co‐treatment with CAPE opposed testosterone‐induced elevation in the level of TNF‐α and NF‐κB activity, which indicated the suppression of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…50 In addition inflammation, activation of NF-κB signaling and subsequent and expression of constitutively active androgen receptor variant 7 have been shown to correlate with both BPH progression and prostate volume. 51 Stromal nodules of BPH contain increased T and B lymphocytes. 52 Elevated levels of inflammatory cells have also been detected in the interstitium and surrounding epithelial glands of human BPH.…”
Section: Etiology Of Bphmentioning
confidence: 99%